The Actual Use of modern Education Technology in a University Teaching (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The current research aims at identifying the extent to which a sample of members of teaching staff in the Faculty of Basic Education / Mustansiriyah University used the modern education technology in their teaching and the extent of their actual use of the variables (academic qualification, academic qualification, specialization and years of experience) Consisting of (10) paragraphs, and was applied to a sample of (96) teaching member during the second semester 2016/2017; The study reached the following results:The use of education technology was below the required level in the employment of the use of modern teaching technology in university teaching.There are statistically significant differences in the use of educational technology due to the variable of academic qualification، specialization and years of experience.There are no statistically significant differences in the use of educational technology due to the variable of scientific qualification.     The statistical processing of the research was done using the statistical program (spss), where the frequencies, percentages, arithmetic averages and standard deviations were used, as well as (Willcoxon test).